2018
DOI: 10.1007/s10562-018-2499-9
|View full text |Cite
|
Sign up to set email alerts
|

Strong Metal–Support Interaction and Reactivity of Ultrathin Oxide Films

Abstract: Noble metal particles supported on transition metal oxides (TMO) may undergo a so-called strong metal-support interaction via encapsulation. This perspective addresses catalytic properties of the metal catalysts in the SMSI state which can be explained on the basis of complementary studies performed on well-defined, metal-supported TMO films. In particular, the results of low temperature CO oxidation revealed the key role of weakly bound oxygen species provided by a two-dimensional ("monolayer") oxide film. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 59 publications
(66 reference statements)
1
27
0
1
Order By: Relevance
“…[ 22,23 ] A special type of surface reconstructions that can happen in an oxygen‐rich environment is the formation of ultrathin oxide overlayers. [ 24–26 ] Beyond transition metal‐based catalysis, such oxidized overlayers have also shown their importance in carbon‐based catalysts. [ 27,28 ] Here, we report that a kinetically stable reconstructed oxide overlayer on Mo 3 P boosts its electrocatalytic performance toward exceptional ORR and OER activities, that is, current densities of 7.21 mA cm −2 at 2.0 V versus Li/Li + (ORR) and 6.85 mA cm −2 at 4.2 V versus Li/Li + (OER) in a non‐aqueous electrolyte, exceeding the performance of existing catalysts reported to date.…”
Section: Figurementioning
confidence: 99%
“…[ 22,23 ] A special type of surface reconstructions that can happen in an oxygen‐rich environment is the formation of ultrathin oxide overlayers. [ 24–26 ] Beyond transition metal‐based catalysis, such oxidized overlayers have also shown their importance in carbon‐based catalysts. [ 27,28 ] Here, we report that a kinetically stable reconstructed oxide overlayer on Mo 3 P boosts its electrocatalytic performance toward exceptional ORR and OER activities, that is, current densities of 7.21 mA cm −2 at 2.0 V versus Li/Li + (ORR) and 6.85 mA cm −2 at 4.2 V versus Li/Li + (OER) in a non‐aqueous electrolyte, exceeding the performance of existing catalysts reported to date.…”
Section: Figurementioning
confidence: 99%
“…For a more exhaustive panorama of this topic the reader is referred to many existing excellent reviews and perspectives such as Refs. 124,[131][132][133][134][135] , to cite some among the most recent ones.…”
Section: Reviewmentioning
confidence: 99%
“…When the encapsulation of metal particles by the FeO bilayer is complete, a way to enhance the catalytic activity is to work under oxygen rich atmosphere and at lower temperatures, when an oxidized FeO 2-x overlayer can be formed which can be catalytically active towards reactions like water dissociation 141 . The debate on the transformations and properties of Pt(111)/FeO x is still open and very active 142 , and a recent review 135 discusses the most recent results on this system in an exhaustive way. Further results on this system comes from Zhang et al 142 , who suggested that both FeO and FeO 2-x overlayers play a role in CO oxidation, and that the reaction takes place at the interface between the reduced and the oxidized phase.…”
Section: Reviewmentioning
confidence: 99%
“…Transmission electron microscopy unambiguously showed the encapsulation of supported PGM catalysts by their metal oxide support [42][43][44][45]. Besides partial wetting or complete encapsulation of metallic nanoparticles by the oxidic support, also the formation of intermetallic compounds or alloys has been observed, especially at very high temperature under reducing conditions [46,47].…”
Section: Introductionmentioning
confidence: 92%